A hybrid method of optimal sensor placement for dynamic response monitoring of hydro-structures. (May 2017) - Chen, Bo; Huang, Zishen; Zheng, Dongjian; Zhong, Liyu
A hybrid method for optimal sensor placement is introduced to position detection sensors on hydro-structures to maximize the monitored structural dynamic information. In the hybrid method, modal assurance criterion matrices and effective independence vectors were applied as the optimization principle for adding and eliminating potential sensor locations in coordinate sets. The energy revision factor was implemented to measure the modal strain energy and ensure the arrangement of sensors at the large energy locations. QR decomposition of the modal matrix was employed to decrease the influence of the initial sensor positions. A computational simulation of an arch dam model, considering 20 sensors and the first six orders of modal vibrations, was used to demonstrate the feasibility of the method. The advantages and disadvantages of existing methods were demonstrated by comparison criteria including the modal assurance criterion, modal kinetic energy criterion, Fisher information matrix, and root-mean square error criterion. The results showed that the method proposed in this article provides linear independent and orthogonal modal vectors, minimizing the relative mean square error of the measured vibration modes, which fundamentally indicates that the identified vibration characteristics of the concrete arch dam are accurate and reasonable.